Digital entrepreneurship: A research agenda on new business models for the twenty-first century. Issue 2 (21st September 2018) - Kraus, Sascha; Palmer, Carolin; Kailer, Norbert; Kallinger, Friedrich Lukas; Spitzer, Jonathan
Abstract : Purpose: Digital entrepreneurship is of high topicality as technological developments and advances in infrastructure create various opportunities for entrepreneurs. Society's great attention to new digital business models is opposed to very little research regarding opportunities, challenges and success factors of digital entrepreneurship. The purpose of this paper is to gather the state-of-the-art literature on digital entrepreneurship and to provide an up-to-date compilation of key topics and methods discussed in the relevant literature. Furthermore, based on findings of the systematic literature review, a research map pointing at further research opportunities for scholars working in the field will be proposed. Design/methodology/approach: Utilising a systematic search and review of literature across the domain whilst following the established methodology of Tranfield et al. (2003) combined with the application of a quality threshold for journal selection, 35 articles on digital entrepreneurship could be found relevant for an evidence-informed literature review. Findings: Based on a conceptual literature review, six streams of research that deal with digital entrepreneurship are identified and discussed: digital business models; digital entrepreneurship process; platform strategies; digital ecosystem; entrepreneurship education; and social digital entrepreneurship. Originality/value: This systematic literature review identifies current research paths on digital entrepreneurship by structuring the dispersed status quo of research in the identified different areas. In addition, future research opportunities to deepen the understanding of digital entrepreneurship are highlighted and pictured in a research map.